Rancang Bangun Sistem Pembatas Akses Pintu Masuk Laboratorium Menggunakan Teknologi Radio Frequency Identification (RFID) dan Keypad - Ahmad Aziz Arrizal; Sri Wahyu Suciyati; Arif Surtono; Gurum Ahmad Pauzi (Journal of Energy, Material, and Instrumentation Technology, 2022)
The laboratory access restriction system has been realized using RFID and keypad technology, based on an Arduino microcontroller as a processor. The system has recorded users who entered the room by identifying the RFID tag (transponder) used to open the door from the outside. As for access outside the room, the user only needs to enter the password as identification data on the keypad, and the system would reduce the number of room users and open the door. The output of this system was a solenoid lock which functions as an electronic lock and an LCD to display the status of the RFID reading. The test results showed that the system created can work well. RFID Reader was able to read tags with a maximum distance of 4 cm. The program counter functions well, so the number of users was limited to 15 (50% of the maximum capacity).